Linking indigenous ecological knowledge to fluvial-territories management in Ecuadorian Andean-Amazonian watersheds - Rosero-López, Daniela; Villamarín, Carla N.; Nenquimo, Gonzalo; Varese, Mariana; Daza, José R.; Encalada, Andrea C. (Frontiers in Environmental Science, 2026)
Long-term monitoring is a crucial asset for informed decision-making in viable ecosystem management. Conservation initiatives involving local stakeholders are receiving increasing support; however, in remote regions such as the Western Amazon, scientific data are often scarce, and conservation efforts rarely integrate Indigenous knowledge into decision-making. To address this gap, this study aims to promote Citizen Science as a bridge between Indigenous communities, their ecological knowledge, and scientific data, thereby advancing environmental management and freshwater ecosystems conservation to the next level. Our case study focuses on the Curaray-Nushiño fluvial system in the Ecuadorian Amazon, home to the ancestral Waorani Indigenous Nationality. This area constitutes a biodiversity hotspot, where communities have relied on the integrity of the fluvial system that supports their livelihoods, which is threatened by anthropogenic pressures. Through the Citizen Science Project of the Alianza Aguas Amazonicas, Waorani monitors collected data, analyzed indicators of water quality, and documented the presence and abundance of edible fish. Data was co-produced through participatory field protocols, integrating community knowledge and scientific methods to inform about the ecological status of streams. Overall, results revealed that local monitors can successfully generate reliable datasets on water quality and fish diversity. This initiative highlights the potential of empowering Indigenous-led participatory freshwater conservation, reinforcing the role of local knowledge in generating and using data to preserve their territories.